EFEKTIVITAS TERAPI BACAAN AL-QUR’AN BERBASIS DIGITAL TERHADAP PENURUNAN STRES MAHASISWA - Maelina Putri Maratu Solihah; Syafi’in Mansur; Muhamad Zaky Hamdie; Wita Wita; Nikhlah Ziyadaturrohmah (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Stress is a prevalent mental health issue among university students, intensified by academic pressures and digital-era challenges. This study aims to examines the effectiveness of Surat Ar-Rahman recitation therapy in reducing stress levels among Muslim students at UIN Banten. Using a quasi-experimental design with pre-test and post-test in one group, 25 purposively sampled students participated by completing digital questionnaires via Google Form before and after listening to the Surat Ar-Rahman murotal through an integrated YouTube audio link. Results indicate a significant reduction in stress, with 85% of respondents reporting increased calmness and relaxation post-therapy. The repeated verse, "Then which of your Lord’s blessings will you deny?" creates a spiritual relaxation effect by activating the parasympathetic nervous system and reducing cortisol levels. The integration of digital technology allows for flexible, personalized, and real-time monitoring of therapy outcomes, making it an effective, scalable alternative to traditional methods. This research supports the use of Qur’anic-based digital therapies as holistic interventions that address mental, spiritual, and physical health in Muslim students facing academic stress in the digital age.